The Subtitle Strategy of Cultural Translation in œMurder on The Orient Express Movie - Saragih, Wiwin Rosari; Manullang, Elisa Betty (Universitas Negeri Medan, 2022)
This research examines the translation strategies used in movie subtitles and their relation to the cultural context. The translation of subtitles on movie is strongly influenced by grammar and culture. To get the right meaning, a translation strategy is needed in translating subtitles on movie that can adjust the cultural context from the source language to the target language. This study aims to find out the subtitle strategy applied in translating the movie subtitle